Requirements for the Implementation of the Covid-19 Vaccine in Karanganyar Surakarta - Betty Sunaryanti (Public Health and Safety International Journal, 2021)
This study discusses vaccination which is a process in the body, where a person becomes immune or immune to a disease so that if one day he is infected with the disease he will not get sick or only experience mild symptoms of pain, usually by giving the vaccine. Vaccination is not only aimed not only at breaking the chain of disease transmission and stopping the epidemic, but also in the long term to eradicate and even eradicate the disease itself. The research method uses a qualitative approach in obtaining descriptive data with data collection techniques, namely conducting library research. According to data from the Health Office of Karanganyar City, Surakarta, that vaccination is carried out in two stages. For the first stage, the Karanganyar Surakarta City Government received around 30,000 Covid-19 vaccines, which in the first stage prioritized health workers and gradually to the public. In the second stage, the Karanganyar Surakarta City Government received 60,000 Covid-19 vaccines. This second level of vaccination was also addressed to public service officers, including civil servants or commonly called ASN, and other government employees. And as contained in the legislation regarding the procurement of Vaccines and the Implementation of Vaccinations in the Context of Combating the Covid-19 Pandemic.